Rogue forces - Brown, Dale, 1956- (William Morrow, 2009)
Scion Aviation International has been hired by the Pentagon to take over aerial patrols in northern Iraq as the U.S. military begins to downsize its presence there. But when Kurdish nationalist attacks led by the Republic of Turkey and joined by the new government in Persia invade northern Iraq, retired Air Force lieutenant-general Patrick McLanahan makes the decision to take the fight to the Turks.